Phaselock techniques. - Gardner, Floyd Martin, 1929- (Hoboken : Wiley, 2005)
The Third Edition of this landmark book presents new developments in the field of phaselock loops, some of which have never been published until now. Established concepts are reviewed critically and recommendations are offered for improved formulations. The work reflects the author's own research and many years of hands-on experience with phaselock loops. Reflecting the myriad of phaselock loops that are now found in electronic devices such as televisions, computers, radios, and cell phones, the book offers readers much new material, including: Revised and expanded coverage of transfer functions Two chapters on phase noise Two chapters examining digital phaselock loops A chapter on charge-pump phaselock loops Expanded discussion of phase detectors and of oscillators A chapter on anomalous phaselocking A chapter on graphical aids, including Bode plots, root locus plots, and Nichols charts As in the previous editions, the focus of the book is on underlying principles, which remain valid despite technological advances. Extensive references guide readers to additional information to help them explore particular topics in greater depth.
Keywords: Fasevergrendeling